Microporous Polyurethane Thin Layer as a Promising Scaffold for Tissue Engineering - Justyna Kucińska-Lipka (Polymers, 2017)
The literature describes that the most efficient cell penetration takes place at 200–500 µm depth of the scaffold. Many different scaffold fabrication techniques were described to reach these guidelines. One such technique is solvent casting particulate leaching (SC/PL). The main advantage of this technique is its simplicity and cost efficiency, while its main disadvantage is the scaffold thickness, which is usually not less than 3000 µm. Thus, the scaffold thickness is usually far from the requirements for functional tissue reconstruction. In this paper, we report a successful fabrication of the microporous polyurethane thin layer (MPTL) of 1 mm thick, which was produced using SC/PL technique combined with phase separation (PS). The obtained MPTL was highly porous (82%), had pore size in the range of 65–426 µm and scaffold average pore size was equal to 154 ± 3 µm. Thus, it can be considered a suitable scaffold for tissue engineering purpose, according to the morphology criterion. Polyurethane (PUR) processing into MPTL scaffold caused significant decrease of contact angle from 78 ± 4° to 56 ± 6° and obtained MPTL had suitable hydrophilic characteristic for mammalian cells growth and tissue regeneration. Mechanical properties of MPTL were comparable to the properties of native tissues. As evidenced by biotechnological examination the MPTL were highly biocompatible with no observed apparent toxicity on mouse embryonic NIH 3T3 fibroblast cells. Performed studies indicated that obtained MPTL may be suitable scaffold candidate for soft TE purposes such as blood vessels.